DOCUMENTARY PHOTOGRAPHY:: A CONTRIBUTION OF GRAPHIC DESIGN TO QUALITATIVE RESEARCH - Zárate Negrete, Laura Elena (UNIVERSIDAD DE SONORA, 2019)
Mining has always been associated with masculinity. In the social imaginary, mining work involves efforts that go beyond feminine capabilities: handling of heavy machinery, risk in the location of explosives, digging in depths with little oxygen and other activities. The idea that only men can deal with heavy work has permeated so much in collective dynamics that the role of women mining has been ignored over time.The objective of this research is to know those voices that have generally been kept underground: that of women miners, and the testimonies of the functions, objectives, adversities, dreams, achievements and experiences of these workers, using documentary photography as evidence of the Field work with the purpose of establishing a link between graphic design and organizational studies.The research was carried out through the case methodology, is descriptive, explanatory and exploratory qualitative approach, using the interview as an instrument of data collection and enriched the evidence through documentary photography; the latter derived from the integration of graphic design as a means of transmitting ideas and symbols.